Social Impact Analysis of the Innovation of the Independent Farmer Program on Farmers' Welfare in Sumberrejo District - Junadi, Junadi; Kumalasari, Ana; Ibrahim, Adil Hassan (PT Mattawang Mediatama Solution, 2024)
The research aims to analyze the social impact of the Independent Farmer Program innovation on the welfare of farmers in Sumberrejo District, Bojonegoro Regency. This qualitative study gathered primary data through interviews with participating farmers and secondary data from official reports. The results indicate that the Independent Farmer Program significantly improves farmers' income, access to technology, and agricultural management skills. It also contributes positively to other social aspects such as education, health, and overall family welfare. However, challenges remain, particularly concerning resources and infrastructure. Recommendations are provided to enhance government support and program sustainability. This study offers insights for policymakers in improving farmers' welfare through innovative programs.